Distribution Dynamics and Roles of Starch in Non-photosynthetic Vegetative Organs of Santalum album Linn., a Hemiparasitic Tree - Zhou, Xiu Ren; Zhang, Ning Nan; Zhao, Yi Min; Dai, Lei; Xu, Da Ping; Xu, Gui Fang; Tian, Jing (Frontiers in Plant Science, 2021)
Starch plays important roles in the development of trees in specific conditions. Many researches have focused on the dynamics and characters of starch of autotrophic trees, however, the corresponding studies on parasitic trees are rarely carried out. In this research, the allocation dynamics and roles of the starch in Santalum album, a hemiparasitic tree, were determined and estimated using morphological and physiological methods. It showed that there was abundant starch in the stem and root at early stages of seedling growth, and that the starch levels in attached seedlings had no significant changes throughout the experiment, but the unattached and re-unattached seedlings exhibited the significant decreases of starch contents with time. In addition, abundant starch accumulated in different zones of a haustorium during its development, and there was much less starch in the inactive haustoria. It suggests that the starch provides energy and substances for the development of unattached seedlings, which possibly extends their survival as much as possible to successfully attach the host roots. It also indicates that the starch may be involved in the haustorium development and the absorption and transportation of water and nutrients from hosts.